Assignment of the Ethnoscience Project "Art of Jidor" in Learning the Concept of Sound for PGSD Students as an Effort to Cultivate 4C - Fanani, Achmad; Rosmiati, Rosmiati; Juniarso, Triman; Purwanti, Camelia Istiqomah; Ula, Syarifatul (JUPE : Jurnal Pendidikan Mandala, 2023)
The aim of this research is to determine the results of the project assignment for making a simple jidor musical instrument and the relationship between the project assignment and the ability to develop 4C skills in PGSD students. The subjects of this research were PGSD students at PGRI Adi Buana University, Surabaya. The data collection technique uses product assignments for simple jidor art imitation tools. The data analysis technique used in this research is descriptive by describing the results of assignments which are supported by the results of literature studies to find connections between project assignments and developing 4C skills. Based on the results obtained, it can be concluded that the jidor art ethno science project assignment in learning sound concepts for PGSD students is able to develop 4C skills well.